Scale‐up of affinity membrane modules: comparison between lumped and physical models1. Issue 3 (6th February 2015) - Dimartino, Simone; Boi, Cristiana; Sarti, Giulio C.; Fleminger, Gideon; Jungbauer, Alois
<x xml:space="preserve">Abstract</x> Membrane chromatography represents one of the emerging technologies for downstream processing in the biotechnology industry. This process is currently used in polishing steps for antibody manufacturing, while its application is still under development for the capture step. To promote its employment in large‐scale processes, it is crucial to develop a simple, yet reliable, simulation tool able to describe the process performance in a predictive way at all scales. In this work, the physical model for the description of protein purification with affinity membrane chromatography has been used to predict the performance of scaled‐up systems and compared with the lumped model, frequently used for its deceptive simplicity. Two commonly used binding kinetics have been implemented in the models, namely the Langmuir and the bi‐Langmuir equations. The two models describe equally well experimental data obtained in a lab‐scale apparatus, while, on the contrary, important differences are observed in scaled‐up systems even at the early stages of breakthrough, which are particularly relevant in industrial‐scale operations. It is seen that for both kinetics, the physical model is more appropriate and safer to use for scale‐up purposes. Copyright © 2015 John Wiley & Sons, Ltd.